Jamaican students' attitude to science as it relates to achievement in external examinations - Hamilton, Marlene A.
Science Attitude was measured by the Moore and Sutman (1970) Science Attitude Inventory and performance at O' and A'Levels of the General Certificate of Education (GCE) examinations were the indices of achievement in this two-phase study. Of 248 boys and 328 girls in the original O'Level sample (1975), 56 boys and 26 girls (more than half of those who proceeded to A'Level) were included in the later (1977) sample. Of the several findings drawn from the data, the study stresses the fact that although at O'Level, there was for both sexes a significant relationship between the O'Level science achievement and science attitude in the fifth form sample overall, for those students classified as high achievers, this relationship existed for the girls only, indicating that for the latter, attitudes may have played a greater role in high level performance than for boys
DOI: 10.1002/sce.3730660203
Keywords: Cambridge GCE Examinations